Argonaute2 attenuates active transcription by limiting RNA Polymerase II elongation in Drosophila melanogaster. Issue 1 (December 2018) - Nazer, Ezequiel; Dale, Ryan; Palmer, Cameron; Lei, Elissa
Abstract Increasing lines of evidence support that Argonaute2 (AGO2) harbors several nuclear functions in metazoa. In particular, Drosophila AGO2 modulates transcription of developmentally regulated genes; however, the molecular mechanisms behind AGO2 recruitment into chromatin and its function in transcription have not been deeply explored. In this study, we show thatDrosophila AGO2 chromatin association depends on active transcription. In order to gain insight into how AGO2 controls transcription, we performed differential ChIP-seq analysis for RNA Polymerase II (Pol II) upon depletion of AGO2. Remarkably, we find specific accumulation of the elongating but not initiating form of Pol II after AGO2 knockdown, suggesting that AGO2 impairs transcription elongation. Finally, AGO2 also affects Negative Elongation Factor (NELF) chromatin association but not the Cyclin Dependent Kinase 9 (CDK9). Altogether, these results provide key insights into the molecular role of AGO2 in attenuating elongation of certain actively transcribed genes.